2014
DOI: 10.1074/jbc.m114.554378
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Nicotinamide Mononucleotide Adenylyltransferase 3 (Nmnat3) Causes Hemolytic Anemia by Altering the Glycolytic Flow in Mature Erythrocytes

Abstract: Background: Nmnat3 is considered a mitochondria-localized NAD synthesis enzyme. However, its physiological function in vivo remains unclear. Results: Loss of Nmnat3 results in drastic depletion of the NAD pool and stalls the glycolytic flow in mature erythrocytes. Conclusion: Nmnat3 deficiency causes splenomegaly and hemolytic anemia in mice. Significance: This report reveals the essential role of Nmnat3 in mature erythrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 63 publications
(68 reference statements)
4
88
0
Order By: Relevance
“…In contrast, NMNAT2 is mostly located in the cytosol and Golgi apparatus (Berger et al, 2005; Yalowitz et al, 2004). Finally, NMNAT3 is highly expressed in erythrocytes with a moderate expression in skeletal muscle and heart, and has been identified in both cytosolic and mitochondrial compartments, with cell/tissue specific subcellular localization patterns (Berger et al, 2005; Felici et al, 2013; Hikosaka et al, 2014; Zhang et al, 2003). The possible implications of the subcellular localization of NMNAT enzymes will be discussed in section 2.3.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, NMNAT2 is mostly located in the cytosol and Golgi apparatus (Berger et al, 2005; Yalowitz et al, 2004). Finally, NMNAT3 is highly expressed in erythrocytes with a moderate expression in skeletal muscle and heart, and has been identified in both cytosolic and mitochondrial compartments, with cell/tissue specific subcellular localization patterns (Berger et al, 2005; Felici et al, 2013; Hikosaka et al, 2014; Zhang et al, 2003). The possible implications of the subcellular localization of NMNAT enzymes will be discussed in section 2.3.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that most endogenous Nmnat3 proteins reside in the cytoplasm (Hikosaka et al., 2014; Yamamoto et al., 2016), although several reports claim that Nmnat3 is present in the mitochondria (Nikiforov et al., 2011; VanLinden et al., 2015). However, we also reported that overexpression of Nmnat3 in HeLa cells encouraged localization of Nmnat3 in mitochondria (Hikosaka et al., 2014). Thus, we examined whether overexpression of Nmnat3 contributes to mitochondrial NAD levels in Nmnat3 Tg mice.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Nmnat3 has been found in the mitochondria and is widely associated with mitochondrial NAD biosynthesis (Berger et al., 2005; Nikiforov et al., 2011; VanLinden et al., 2015). Although Nmnat3 deficiencies in mice caused no obvious changes in mitochondrial NAD levels, suggesting redundancy between mammalian Nmnat isozymes (Hikosaka et al., 2014; Yamamoto et al., 2016), overexpression of Nmnat3 in human cultured cells reportedly contributed to mitochondrial NAD synthesis (Nikiforov et al., 2011). These data suggest that overexpression of Nmnat3 can increase mitochondrial NAD levels and stimulate mitochondrial metabolism in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…7, 8). Of note, NMNAT3 knockout mice appear viable,41 although it is not yet known whether these mice have abnormalities in neuronal development or survival under basal or injurious conditions. Lastly, increases in endogenous NMNAT3 24 h following H‐I were primarily observed in the hypoxic side of the pup brain.…”
Section: Discussionmentioning
confidence: 99%